Preventive measures and associated factors of respiratory illness among Malaysian pilgrims 2013 - Hashim, Suhana (2016)
Background: Respiratory illness continues to exert a burden on hajj pilgrims in Makkah. The purpose of this study is to determine the prevalence of respiratory illness and its associated factors among Malaysian hajj pilgrims in 2013 and to describe its preventive measures. Methods: A cross-sectional study was conducted in Makkah and Malaysia during the 2013 hajj season. A self-administered form on social demographics, previous experience of hajj or umrah, smoking habits, co-morbid illness and practices of preventive measures against respiratory illness and ILI were obtained. Altogether 468 forms were analysed. Results: The prevalence of the respiratory illness was 93.4% with a subset of 78.2% fulfilled the criteria for influenza-like illness (ILI). Most of them (77.8%) had a respiratory illness of less than 2 weeks duration. About 61.8% were administered antibiotics, but only 2.1% of them had been hospitalized. Most of them acquired the infection after a brief stay at Arafat (81.2%). Vaccination coverages for influenza virus and pneumococcal disease were quite high, 65.2% and 59.4% respectively. For other preventive measures practices, only 31.8% of them practiced good hand hygiene. Three hundred and twenty two of our pilgrims had worn standard face masks (83.0%) and outof these numbers, 45.3% of them used in proper way. Malaysian hajj pilgrims with previous experience of hajj (OR 0.24; 95% CI 0.10-0.56) or umrah (OR 0.19; 95% CI 0.07-0.52) were significantly associated with lower risk of respiratory illness. Otherwise, pilgrims having contact with those with respiratory illness (OR 3.01; 95% CI 1.35-6.68) were associated with higher risk. Malaysian hajj pilgrims with previous experienced of hajj (OR 0.26; 95% CI 0.15-0.46) were protected from ILI while those who suffered from bronchial asthma (OR 7.27; 95% CI 0.96-54.94) were found to be significantly associated with higher risk of getting ILI. Conclusions: The prevalence of respiratory illness remains high among Malaysian hajj pilgrims despite having some practices of preventive measures. All preventive measures which include hand hygiene, wearing face masks and influenza vaccination must be practiced together as bundle of care to reduce respiratory infections effectively.